Kidney ion handling genes and their interaction in blood pressure control. Issue 11 (16th November 2022) - An, Caiyan; Yang, Liuyi; Han, Tengfei; Song, Huazhong; Li, Zichao; Zhang, Junjing; Zhang, Kejin
Abstract: Hypertension affects 30% of adults and is the leading risk factor for cardiovascular disease. Kidney sodium reabsorption plays a vital role in the initial stage and development of essential hypertension. It has been extensively reported that the variants of kidney ion handling genes are associated to blood pressure, and clinical features of hypertension. However, the underlying mechanisms by which these variants alter protein function are rarely summarized. In addition, the variation of one single gene is often limited to induce a significant effect on blood pressure. In the past few decades, the influence by genes × genes (G × G) and/or genotype × environment (G × E) interactions on a given trait, for example, blood pressure, have been widely considered, especially in studies on polygenic genetic traits. In the present review, we discuss the progress in genetics studies on kidney ion handling genes, encoding Na + channels (Na + -Cl − cotransporter [NCC], Na-K-2Cl cotransporter [NKCC2], epithelial Na + channels [ENaCs]), K + channel (renal outer medullary potassium channel [ROMK]), and Cl − channels (Pendrin, chloride voltage-gated channel Kb [CLC-Kb]), respectively, and their upstream kinases, WNKs and SGK1. We seek to clarify how these genes are involved in kidney sodium absorption and influence blood pressure, especially emphasizing the underlying mechanisms by which genetic variants alter protein functions and interaction in blood pressure regulation. The present review aims to enhance our understanding of the important role of kidney ion handling genes/channels in blood pressure control.